Matriptase-2 and Hemojuvelin in Hepcidin Regulation: In Vivo Immunoblot Studies in Mask Mice - Krijt, Jan; Frýdlová, Jana; Gurieva, Iuliia; Přikryl, Petr; Báječný, Martin; Steinbicker, Andrea U; Vokurka, Martin; Truksa, Jaroslav (International journal of molecular sciences, 2021)
Matriptase-2, a serine protease expressed in hepatocytes, is a negative regulator of hepcidin expression. The purpose of the study was to investigate the interaction of matriptase-2 with hemojuvelin protein in vivo. Mice lacking the matriptase-2 proteolytic activity (mask mice) display decreased content of hemojuvelin protein. Vice versa, the absence of hemojuvelin results in decreased liver content of matriptase-2, indicating that the two proteins interact. To further characterize the role of matriptase-2, we investigated iron metabolism in mask mice fed experimental diets. Administration of iron-enriched diet increased liver iron stores as well as hepcidin expression. Treatment of iron-overloaded mask mice with erythropoietin increased hemoglobin and hematocrit, indicating that the response to erythropoietin is intact in mask mice. Feeding of an iron-deficient diet to mask mice significantly increased spleen weight as well as the splenic content of erythroferrone and transferrin receptor proteins, indicating stress erythropoiesis. Liver hepcidin expression was decreased; expression of Id1 was not changed. Overall, the results suggest a complex interaction between matriptase-2 and hemojuvelin, and demonstrate that hepcidin can to some extent be regulated even in the absence of matriptase-2 proteolytic activity.
Keywords: játra; Hemochromatosis Protein; Membrane Proteins; Iron Overload; Promoter Regions, Genetic; erythropoetin; Serine Endopeptidases; regulace genové exprese; Female; Organ Specificity; hepcidiny; neogenin; proteinové domény; Erythropoietin; zvířata; Recombinant Proteins; myši; GPI-Linked Proteins; Tfrc; Bone Morphogenetic Protein 6; myši inbrední C57BL; dietní železo; Hepcidins; Inhibitor of Differentiation Protein 1; Mice; Tmprss6; myši knockoutované; rekombinantní proteiny; ženské pohlaví; Gene Expression Regulation; Liver; serinové endopeptidasy; Male; Mice, Knockout; Tfr2; Iron, Dietary; Spleen; inhibitor diferenciace 1; Mice, Inbred C57BL; protein hemochromatózy; Protein Domains; transferrin receptor; kostní morfogenetický protein 6; membránové proteiny; Hjv; Animals; přetížení železem; GPI-vázané proteiny; deficit železa; mužské pohlaví; orgánová specificita; promotorové oblasti (genetika); Iron Deficiencies; hepcidin; slezina